2021
DOI: 10.1038/s41598-021-83560-y
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-based proteomics reveals novel binding partners for Rab46 in endothelial cells

Abstract: Rab46 is a novel Ca2+-sensing Rab GTPase shown to have important functions in endothelial and immune cells. The presence of functional Ca2+-binding, coiled-coil and Rab domains suggest that Rab46 will be important for coupling rapid responses to signalling in many cell types. The molecular mechanisms underlying Rab46 function are currently unknown. Here we provide the first resource for studying Rab46 interacting proteins. Using liquid chromatography tandem mass spectrometry (LC–MS/MS) to identify affinity pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Rab4a strongly recruited Rab6 (Rab6A:Rab6B:Rab39; protein group not distinguishable by MS/MS) and Rab7a, suggesting interplay between these trafficking routes (Figure 2). Furthermore, Rab11a and Rab25 recruited the related GTPases Arl13b (Figure 2), RABL6 (longlist only, Supplementary Table 2) and CRACR2A (Rab46), a dynein adaptor which can play a role in the stimulated release of Weibel-Palade bodies in endothelial cells (Miteva et al, 2019; Pedicini et al, 2021; Wang et al, 2019). Taken together these data give confidence that BioID is an excellent technique to capture and compare Rab interactions in live cells.…”
Section: Resultsmentioning
confidence: 99%
“…Rab4a strongly recruited Rab6 (Rab6A:Rab6B:Rab39; protein group not distinguishable by MS/MS) and Rab7a, suggesting interplay between these trafficking routes (Figure 2). Furthermore, Rab11a and Rab25 recruited the related GTPases Arl13b (Figure 2), RABL6 (longlist only, Supplementary Table 2) and CRACR2A (Rab46), a dynein adaptor which can play a role in the stimulated release of Weibel-Palade bodies in endothelial cells (Miteva et al, 2019; Pedicini et al, 2021; Wang et al, 2019). Taken together these data give confidence that BioID is an excellent technique to capture and compare Rab interactions in live cells.…”
Section: Resultsmentioning
confidence: 99%
“…Rab45 and Rab46 contain two EFDs (Figure 1). The second EFD of Rab46 reportedly binds to Ca 2+ [23,24]. The EFDs of Rab45 have not been investigated.…”
Section: Common Features Of Large Rab Gtpasesmentioning
confidence: 99%
“…The PRD of Rab46 associates with the SH3-SH2-SH3 domains of Vav1, wherein Vav1 is tyrosine-phosphorylated after TCR stimulation [35]. Recently, it has been found that Rab46 directly binds to the motor protein dynein-dynactin complex [24,25,58], and the Na 2+ /K + ATPase subunit alpha 1 in endothelial cells [24].…”
Section: Binding Molecules And/or Effectorsmentioning
confidence: 99%
“…1a ) [ 8 ]. Rab46 is necessary for stimuli-coupled trafficking of a sub-population of endothelial-specific vesicles to the microtubule organizing center [ 9 , 10 ] and for vesicle translocation to the immunological synapse in T-cells [ 11 ]. Here, we investigated the role of Rab46 in regulating mast cell degranulation and in establishing the pro-inflammatory environment typical of many immune-related diseases.…”
Section: Introductionmentioning
confidence: 99%